Reliability and Validity of the Chinese Version of the Parental Acceptance Questionnaire (6‐PAQ) Among Parents of Children With or Without Hearing Loss - Sini LI; Jianhe LI; Yamin Li; Jiao Xie (Journal of Clinical Psychology, 2026)
ABSTRACT Background The parental acceptance questionnaire (6‐PAQ) is a user‐friendly and contextually sensitive scale of psychological flexibility. Objective This research aimed to translate the original English version of the 6‐PAQ into Chinese and to test its psychometric properties among Chinese parents of children with or without hearing loss (HL). Methods Two phases were conducted: (1) translation from English to Chinese (6‐PAQ‐C), followed by a semantic equivalence evaluation between two versions, a pre‐test and face validity with 40 parents of children with or without HL, and content validity with 15 experts; (2) A cross‐sectional study was conducted for providing empirical support among two samples: parents of children with ( n = 204) or without ( n = 336) HL. All participants were assessed for test–retest reliability over an 8‐week interval. Results The 6‐PAQ‐C showed satisfactory semantic equivalence with the original version, excellent internal consistency, and good 8‐week test–retest stability. Exploratory factor analysis and parallel analysis confirmed a six‐factor structure consisting of 18 items. Confirmatory factor analysis supported both the original six‐factor structure and a bifactor model (one general factor plus six specific factors), both demonstrating excellent fit. Bifactor indices indicated a strong general factor (omega = 0.95; omega hierarchical = 0.80; proportion of uncontaminated correlations = 0.88) and more modest independent specific‐factor reliability (omega hierarchical subscale = 0.41–0.49; specific explained common variance = 0.08–0.10), supporting use of the total score as the primary metric and subscale scores as supplementary indicators. The scale also exhibited significant mean score differences between parents with high and low parenting stress in both samples and correlated with measures of psychological flexibility, symptomatology, and mental well‐being. Conclusions These findings suggest that the 6‐PAQ‐C is a reliable and valid instrument for measuring psychological flexibility among parents of children with or without HL. In practice, the total score should be treated as the primary scoring metric, whereas the six subscale scores may be used cautiously to describe ACT process profiles rather than as fully independent dimensions. Future research should test the 6‐PAQ‐C with diverse samples across cultures/contexts to improve its generalizability.